PENGARUH EXPERIENTIAL MARKETING TERHADAP LOYALITAS PELANGGAN - RASNI, RASNI (Fakultas Ekonomi Universitas Tadulako, 2018)
This study aims to) determine the influence of experiential marketing both simultaneously and partially to customer loyalty Roxy Mart Palu City. The independent variables used in this research are sense, feel, think, act, and relate. While the dependent variable is Customer Loyalty. The method used in this research is quantitative descriptive method. The type of research conducted is descriptive causal. The sample is 90 respondents with purposive sampling sampling technique. Data analysis method used in this research is multiple linear regression analysis method using SPSS 23. The result of this research shows that simultaneously experiential marketing consisting of sense, feel, think, act, and relate significantly influence customer loyalty Roxy Mart Palu City . Partially customer trust consisting of sense, feel, think, act, and relate have a significant effect to customer loyalty Roxy Mart Palu City.